ChemInform Abstract: Hydroflux Crystal Growth of Platinum Group Metal Hydroxides: Sr6NaPd2(OH)17, Li2Pt(OH)6, Na2Pt(OH)6, Sr2Pt(OH)8, and Ba2Pt(OH)8. Issue 22 (13th May 2013) - Bugaris, Daniel E.; Smith, Mark D.; zur Loye, Hans‐Conrad
Abstract Single crystals of the title compounds are prepared in essentially quantitative yield by a new hydroflux method.